2002
DOI: 10.1016/s0092-8674(02)00691-8
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the Cell Plate in Plant Cytokinesis Requires a Kinesin-like Protein/MAPKKK Complex

Abstract: The tobacco mitogen-activated protein kinase kinase kinase NPK1 regulates lateral expansion of the cell plate at cytokinesis. Here, we show that the kinesin-like proteins NACK1 and NACK2 act as activators of NPK1. Biochemical analysis suggests that direct binding of NACK1 to NPK1 stimulates kinase activity. NACK1 is accumulated specifically in M phase and colocalized with NPK1 at the phragmoplast equator. Overexpression of a truncated NACK1 protein that lacks the motor domain disrupts NPK1 concentration at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
254
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(266 citation statements)
references
References 51 publications
12
254
0
Order By: Relevance
“…The kinesin NACK1 of tobacco (Nicotiana tabacum) contains two MSA sequences in the promoter region that are responsible for mitosisdependent expression [11]. Accordingly, the NACK1 protein accumulates during M-phase, which is consistent with its function in cell plate expansion [12]. The MSA element is absent in the immediate upstream region of kinesins At4g21270, At4g05190 and At5g27550, suggesting that either the MSA sequence has degenerated beyond computer-assisted recognition or another mitosisspecific element exists for the expression of these particular kinesins.…”
Section: Specialized Kinesins For Mitotic Plant Cellsmentioning
confidence: 87%
See 3 more Smart Citations
“…The kinesin NACK1 of tobacco (Nicotiana tabacum) contains two MSA sequences in the promoter region that are responsible for mitosisdependent expression [11]. Accordingly, the NACK1 protein accumulates during M-phase, which is consistent with its function in cell plate expansion [12]. The MSA element is absent in the immediate upstream region of kinesins At4g21270, At4g05190 and At5g27550, suggesting that either the MSA sequence has degenerated beyond computer-assisted recognition or another mitosisspecific element exists for the expression of these particular kinesins.…”
Section: Specialized Kinesins For Mitotic Plant Cellsmentioning
confidence: 87%
“…For several plant kinesins, protein levels have been investigated throughout the cell cycle in synchronized Bright Yellow-2 (BY-2) cells [12,[29][30][31]. The protein levels …”
Section: Specialized Kinesins For Mitotic Plant Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of studies using tobacco BY-2 (Nicotiana tabacum cv. Bright Yellow 2) cell line revealed that the MAP kinase cascade (NACK-PQR pathway) is required for phragmoplast expansion and for cell plate formation (Nishihama et al 2001;Nishihama et al 2002;Soyano et al 2003;Sasabe et al 2006). NACK kinesins activate the MAP kinase cascade, which consists of NPK1 mitogen-activated kinase kinase kinase (MAPKKK), NQK1 MAP kinase kinase (MAPKK), and NRK1 MAP kinase (MAPK).…”
Section: Phosphorylation-dependent Microtubule Regulation In Mitosismentioning
confidence: 99%